PENGARUH AKTIVA PRODUKTIF DAN RENTABILITAS TERHADAP PERTUMBUHAN LABA PADA PERBANKAN DI INDONESIA - Muhtasar, Sri Rezky Hadayani (Universitas Muhammadiyah Parepare, 2020)
The effect of productive asset and rentability toward profit growth on the banks in Indonesia. This research aims to know: the effect of productive asset proxied by Non Performing Loan (NPL) toward profit growth and the effect of rentability proxied by return on asset (ROA) toward profit growth. This research used secondary data. The data used is bank’s publicated annual reports on the period of 2011 until 2015. The total of samples gathered is 15 banks registered in Indonesia Stock Exchange on the period of 2011 until 2015 taken through purposive sampling. The analysis technique used is multiple regression analysis supported by SPSS program version 21.The result shows that: Non Performing Loan (NPL) has insignificantly positive effect toward profit growth and Return on Asset (ROA) has insignificantly positive effect toward profit growth toward profit growth.